Keluarga Sebagai Pendidikan Utama Bagi Anak dalam Perspektif Al-Qur’an - Himatun Aliyah; Mukroji Mukroji (Tarbiatuna: Journal of Islamic Education Studies, 2024)
Education is an effort to provide or transfer knowledge to other people systematically and continuously. One of the most important education is family education where parents have an important role in educating and guiding their children on the right path. Family is the first place for children to learn. A child will form a personality and a way of looking at things based on what he sees and learns in the family environment. In Islamic family education, it has been taught systematically and as well as possible, the foundation that can be an example is in the Al-Qur'an in Surah At-Tahrim verse 66, Surah Luqman verse 13, and Surah Thaha verse 132. The research in this article is included in a type of literature research that is library in nature or library research that uses content analysis as a research approach. This article explains the urgency and objectives of family education itself. Apart from that, it provides an explanation of the teaching methods, namely the example method, advice method, question and answer method, discussion method and also the punishment method. The material that parents must provide to their children in family education, namely monotheism or aqidah education, worship education and finally moral education.